2015
DOI: 10.1016/j.bandl.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Neural changes associated with semantic processing in healthy aging despite intact behavioral performance

Abstract: Semantic memory recruits an extensive neural network including the left inferior prefrontal cortex (IPC) and the left temporoparietal region, which are involved in semantic control processes, as well as the anterior temporal lobe region (ATL) which is considered to be involved in processing semantic information at a central level. However, little is known about the underlying neuronal integrity of the semantic network in normal aging. Young and older healthy adults carried out a semantic judgment task while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 69 publications
(107 reference statements)
6
23
0
Order By: Relevance
“…We observed that L AP asymmetry was higher for older participants than younger ones, suggesting the use of a semantic strategy to perform naming with aging. Our findings are in line with Ansado et al (2013) and Lacombe et al (2015), as these authors suggest that older participants rely on preserved semantic mechanisms by over-recruiting left temporo-parietal regions to perform the task. We posit that this result, referred as the left anterior-posterior aging effect (LAPA), reflects a domain-specific (linguistic) strategy to maintain performance in older adults for tasks involving semantic processes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed that L AP asymmetry was higher for older participants than younger ones, suggesting the use of a semantic strategy to perform naming with aging. Our findings are in line with Ansado et al (2013) and Lacombe et al (2015), as these authors suggest that older participants rely on preserved semantic mechanisms by over-recruiting left temporo-parietal regions to perform the task. We posit that this result, referred as the left anterior-posterior aging effect (LAPA), reflects a domain-specific (linguistic) strategy to maintain performance in older adults for tasks involving semantic processes.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the semantic hypothesis, using functional magnetic resonance imaging (fMRI), Baciu et al (2016) reported higher supplementary bilateral posterior temporo-parietal activity for object naming in older adults compared to younger adults, suggesting greater involvement of lexico-semantic processes. This is in agreement with findings from Ansado et al (2013) for lexical production, and Lacombe et al (2015) for language comprehension. In addition, Lacombe et al (2015) reported that increased posterior activity observed in older adults reflects age-related reorganization of networks responsible for the conceptual retrieval and semantic representations of words.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…These two converging pieces of evidence would suggest that, if anything, ageing should result in a prominent lexical-semantic decline. Instead, only a moderate decrease is detected, and there are studies showing either no effects [40], or even improvement with age [41]. In part, this counterintuitive observation could be due to neural compensation that is present in wellfunctioning older people.…”
Section: Language As Gateway To Semantic Memory In Healthy Ageing and Admentioning
confidence: 99%